2017
DOI: 10.1002/jat.3477
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and carbon nanotubes activate different cell surface receptors on macrophages before and after deactivation of endotoxins

Abstract: Nanomaterial synthesis and handling in a non-sterile environment can result in the final product becoming contaminated with bacterial endotoxin or lipopolysaccharides (LPB). During toxicological testing, the effects caused by endotoxin-contaminated nanomaterials can be misinterpreted in the end-point analysis (such as cytotoxicity and immune responses) and could result in erroneous conclusions. The objective of this study was twofold: (i) to test different carbonbased nanomaterials (CBNs) [pristine graphene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…Indeed, carbon-based nanomaterials including GBMs were shown to interfere with the LAL assay, which may lead to erroneous results or mask the effects of the materials themselves (23, 24). In a recent study, the authors suggested that repeated cycles of autoclaving may reduce the endotoxin content of carbon-based nanomaterials including pristine graphene and that the native versus depyrogenated materials elicited distinct macrophage responses in vitro (25). However, the chromogenic LAL assay was employed to assess for endotoxin contamination, calling into question whether the proposed depyrogenation procedure worked (25).…”
Section: The Importance Of Endotoxin Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, carbon-based nanomaterials including GBMs were shown to interfere with the LAL assay, which may lead to erroneous results or mask the effects of the materials themselves (23, 24). In a recent study, the authors suggested that repeated cycles of autoclaving may reduce the endotoxin content of carbon-based nanomaterials including pristine graphene and that the native versus depyrogenated materials elicited distinct macrophage responses in vitro (25). However, the chromogenic LAL assay was employed to assess for endotoxin contamination, calling into question whether the proposed depyrogenation procedure worked (25).…”
Section: The Importance Of Endotoxin Assessmentmentioning
confidence: 99%
“…In a recent study, the authors suggested that repeated cycles of autoclaving may reduce the endotoxin content of carbon-based nanomaterials including pristine graphene and that the native versus depyrogenated materials elicited distinct macrophage responses in vitro (25). However, the chromogenic LAL assay was employed to assess for endotoxin contamination, calling into question whether the proposed depyrogenation procedure worked (25). TLR4 reporter cells were suggested as an alternative assay to evaluate endotoxin contamination of metal/metal oxide nanoparticles (21).…”
Section: The Importance Of Endotoxin Assessmentmentioning
confidence: 99%
“…For example, one group failed to detect the secretion of tumor necrosis factor alpha (TNF‐α) in human monocyte‐derived macrophages (HMDM) stimulated with endotoxin‐free GO . Furthermore, Lahiani et al reported contrasting results before and after endotoxin deactivation on graphene‐based materials, based on gene expression profiling in macrophages. Some innate cells, such as dendritic cells or macrophages, are able to sense contaminating pathogen‐associated microbial patterns (PAMPs) present on biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Several cell types that are known targets for viruses and/or provide defense against viral infections have been shown to engulf NMs where the cell fate depends on the type of particle, dose, and cell type. For example, NMs can be phagocytosed and degraded by pulmonary macrophages (Lahiani et al 2017;Meng et al 2015), epithelial cells (Foldbjerg et al 2014), brain microglia cells (Shigemoto-Mogami et al 2016), and lymphocytes (Brown et al 2007), among others. Macrophages and epithelial cells usually serve as first-line defense barriers for viral infections of the respiratory tract, and elsewhere, where they engulf NMs and activate cellular signaling pathways to induce inflammatory responses (Pondman et al 2015).…”
Section: Interaction Of Nms With Host Cellsmentioning
confidence: 99%
“…Additionally, noninfectious stimuli from either "self" or the environment, including hydrophobic regions of CNTs, may be categorized as danger-associated molecular patterns (DAMPs), which are involved in the activation of NLR pathways (Silva et al 2017;Mason et al 2012). Interestingly, one study found different profiles of gene expression for TLR signaling, NLR signaling, and downstream signal transduction between CNTs and their depyrogenized versions, indicating the possibility of endotoxin or microbial contamination of CNTs leading to misinterpretation of PRR activation by CNTs (Lahiani et al 2017). Importantly, the ability of NMs to impact PRRs specific to viruses (i.e., TLR3) has not been as well studied.…”
Section: Activation Of Pattern Recognition Receptors (Prrs) and Relatmentioning
confidence: 99%